Enzymatic biosensors for spermidine amperometric determination - Marques, Francisco Soares (2015)
Polyamines (PA) detection has been shown of great interest as biomarkers for various analytical purposes, such as freshness of fish, fruit and vegetables and cancer control. Various methods have been developed for separation and quantification of biogenic amines and among then all, electrochemical biosensors. These types of biosensors, particularly the ones involving the screen-printing technology, which combine construction simplicity with biological recognition through enzyme specificity, have been reported as a good and cheap alternative to the traditional techniques. Screen-printing technology offers design flexibility, process automatization and good reproducibility in the transducers fabrication, as well as the possibility of using a wide choice of materials. In this work, Monoamine Oxidase (MAO) and Diamine Oxidase (DAO) based biosensors using screen-printed carbon electrodes have been attempted for the determination spermidine. The enzymes have been immobilized onto the working electrode by means of glutaraldheyde and chronoamperometric variables (applied potential and solution pH) adjusted for better reply as experimental variables can affect biosensor chronoamperometric response. One form of screen-printed electrodes (SPEs) modification consists of the incorporation of metallic nanoparticles on the working electrode surface. Due to their reduced size, metallic nanoparticles exhibit important physical and electrical properties which make them very useful for the construction of more sensitive electrochemical biosensors. Silver and gold nanoparticle-modified carbon SPEs show important advantages when they are used as working electrodes in electrochemical techniques. Thus, different experiments were performed using modified nanoparticles DAO/MAO biosensors in order to evaluate nanoparticles influence on detection limit, sensibility, repeatability and reproducibility. Isothermal titration microcalorimetry (ITC) may be used as a tool for obtaining overall apparent molar enthalpy for catalytic reactions and enzyme kinetic constants. ITC is useful, in this regard, since it directly measures the heat change as catalysis proceeds and this is proportional to the rate of the reaction. ITC is a well established, powerful, versatile and high-sensitivity technique that is widely used for measuring the thermodynamics of equilibrium association reactions. In addition, well designed experiments can yield an approximate value for the equilibrium association constant for the enzyme-substrate complex (KA) when product formation is the limiting step, as well as the reaction stoichiometry (n). Thus, this technique has been tried to study MAO activity when immobilized on a non-modified SPE.